Minimal closed sets and maximal closed sets - Fumie Nakaoka; Nobuyuki Oda (International Journal of Mathematics and Mathematical Sciences)
Some properties of minimal closed sets and maximal closed sets are obtained, which are dual concepts of maximal open sets and minimal open sets, respectively. Common properties of minimal closed sets and minimal open sets are clarified; similarly, common properties of maximal closed sets and maximal open sets are obtained. Moreover, interrelations of these four concepts are studied.